Scalability of CPU and GPU Solutions of the Prime Elliptic Curve Discrete Logarithm Problem - Panetta, Jairo; SouzaFilho, Paulo R. P.; Laranjeira, Luiz A. F.; Teixeira, Carlos A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2017)
Elliptic curve asymmetric cryptography has achieved increased popularity due to its capability of providing comparable levels of security as other existing cryptographic systems while requiring less computational work. Pollard Rho and Parallel Collision Search, the fastest known sequential and parallel algorithms for breaking this cryptographic system, have been successfully applied over time to break ever-increasing bit-length system instances using implementations heavily optimized for the available hardware. This work presents portable, general implementations of a Parallel Collision Search based solution for prime elliptic curve asymmetric cryptographic systems that use publicly available big integer libraries and make no assumption on prime curve properties. It investigates which bit-length keys can be broken in reasonable time by a user that has access to a state of the art, public HPC equipment with CPUs and GPUs. The final implementation breaks a 79-bit system in about two hours using 80 GPUs and 94-bits system in about 15 hours using 256 GPUs. Extensive experimentation investigates scalability of CPU, GPU and CPU+GPU runs. The discussed results indicate that speed-up is not a good metric for parallel scalability. This paper proposes and evaluates a new metric that is better suited for this task.